An Accountability Design for School Systems - Forehand, Garlie A.; Educational Testing Service, Princeton, NJ. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
A comprehensive plan for accountability in elementary and secondary schools is described. The primary purpose of the accountability system is to promote student development. During the first phase of accountability, an assessment is made of student performance. Results can be expressed in terms of both the percentage of students scoring below minimum performance standards and the Student Development Index, a deviation measure of performance based on longitudinal student data. In the diagnostic phase a systematic study of process variables is initiated to identify those process variables that should become the focus of corrective action plans. Corrective action must then be taken. Suggestions for implementing the accountability system are also presented. (Author)
ERIC Note: Draft Copy.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Accountability; Achievement Tests; Administrator Guides; Educational Diagnosis; Models; Performance Criteria; Program Design; Public Schools; School Districts; Student Evaluation